ANALISIS SUKU BUNGA KREDIT KEPADA KONSUMEN PADA PT.TRIDJAYA MULIA SUKSES MANADO - KARAMOJ, INKE LUPITA; Tumbel, Tinneke M.; SUMAMPOUW, HARRY J. (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
We know that every company aims to survive and thrive. Goals can be achieved throughefforts to maintain and even increase profits. Profits can only be achieved if the companycan maintain and increase the sales volume of goods and services sold. The purpose of thisstudy is to determine the effect of lending rates to consumers. The interest rate is the priceof the use of money or loan services or can also be viewed as rent or use of certain termmoney. And the consumer is any user of goods / services available in the community eitherfor their own interests, family, or other living creatures. The type of research used in thisstudy is quantitative research. Based on the results of research on PT.Tridjaya MuliaSuccess when the money or the amount of money is greater than the amount of moneyneeded then the price of goods or services will tend to rise and vice versa. If the inflationrate creeps up, the interest rate or the price of money offered will tend to increase.Keywords: Interest Rate of Credit to Consumer